Características dendrométricas, químicas e densidade básica da madeira de híbridos de Eucalyptus grandis x Eucalyptus urophylla - Hsing, Tseng Yao [UNESP]; de Paula, Nadia Figueiredo; de Paula, Rinaldo César [UNESP] (My University, 2016)
The present study evaluated the dendrometric, chemical and basic density wood from five hybrids of Eucalyptus grandis x Eucalyptus urophylla at 2.25 years old. The experiment was implemented in 3.5 x 2 meters spacing, with 35 replicates of a single tree. Four replicates were harvester, we evaluated the diameter at breast height (DBH, 1.3 m above the ground), total and commercial height, biomass of leaves, branches, wood and bark, volume with and no bark and volume of bark. Besides it was obtained discs at 0, 25, 50, 75 e 100% of commercial height and at DBH for the determination of wood density and chemical characterization of wood. Data were subjected to analysis of variance and comparison of means by Tukey’s test at 5 % probability. Clones of Eucalyptus grandis x Eucalyptus urophylla exhibited different growth highlighting the C5 with greater volumetric and biomass. The basic density wood is higher when assessed at base of tree, but it was verified similar values in other positions of the stem. Among the clones, the basic density wood of C5 is higher than C3 and C4 and C2 is higher than C3. The chemicals wood characteristics were similar among clones of Eucalyptus grandis x Eucalyptus urophylla. Despite the evaluation have been performed on young plants, 2.25 years old, the clones have demonstrated satisfactory potential in Jaboticabal, SP.
Dendrometric and chemical traits and basic density wood of Eucalyptus grandis X Eucalyptus urophylla hybrids
Keywords: Biomass; Chemical constituents of wood; Eucalyptus; Volume; Wood density